1976
DOI: 10.1111/j.1439-0418.1976.tb04215.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of immature stages of noctuid moths to juvenoids

Abstract: Acetone solutions containing 0.01% or more of juvenoids inhibit hatching when administered to freshly laid eggs of Spodoptera littoralis and Mamestra brassicae. Application of 1–100 μg of juvenoids to penultimate instar larvae of these species induces light body coloration in the last instar larvae. The effect on body coloration, however, is ambiguous in Autographa gamma. Metamorphosis is most readily inhibited by administering juvenoids within the second half of the feeding period in the last larval instar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Procedures for the rearing of the moth were described in detail by Sehnal et al [20]. Eggs, larvae and adults were used in our experiments.…”
Section: Insect Culturementioning
confidence: 99%
“…Procedures for the rearing of the moth were described in detail by Sehnal et al [20]. Eggs, larvae and adults were used in our experiments.…”
Section: Insect Culturementioning
confidence: 99%
“…strain was reared at 25±1°C with 70-80% relative humidity under a L16: D8 photoperiod in the laboratory. This strain was reared for more than 12 subsequent generations under above conditions as described by Sehnal et al, (1976).…”
Section: -Spodoptera Littoralis Culturementioning
confidence: 99%
“…Inhibition of metamorphosis and induction of surplus larval development by juvenoids is accompanied by acceleration of moulting (SLAMA et al 1974). O n the other hand, low and moderate doses of juvenoids, which fail to elicit a morphological effect, often cause a considerable prolongation of the last larval instar of Holometabola (SEHNAL 1976). These observations led SLAMA (1975) to conclude that juvenoids interfere with ,,the hysiological programming of the secretory functions of the prothoracis glan s s." Several authors (NIJHOUT and WILLIAMS 1974;CHIPPENDALE 1977;TAKEDA 1978) suggested that the delay of moult is due to inhibitory action of juvenoids on the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenoids applied to caterpillars frequently extend the period of larval growth (BRIEGER 1973;PLANTEVIN 1975;SILHACEK and OBERLANDER 1975;KRYSPIN et al 1977;SEHNAL et al 1976). Prolongation of larval feeding has a great practical significance because increased food consum tion would hamper the use of juvenoids against many insect pests.…”
Section: Introductionmentioning
confidence: 99%